Antibacterial and anticancer activities of cardamom volatile oil and its application in food covering - Alqahtani, Tahani M.; G. R. Ebrahim, Ebtisam; Aloufi, Abeer S.; El-Saadany, Sayed S.; Almanzalawi, Enas A.; Awad, Ahmed; Eldeeb, Gehad S.; M. El-Maghraby, Lamiaa (Italian Journal of Food Science, 2024)
Phytochemicals and bioactive compounds in medicinal plants significantly benefit human health and well-being. Cardamom essential oil (CEO) exhibits potential as a broad-spectrum antimicrobial and anticancer agent. A modified Kirby-Bauer disc diffusion technique was used to test cardamom essential oil’s antimicrobial activity and identify the inhibition zone. Staphylococcus aureus (ATCC 6538) and Bacillus cereus (ATCC6629) are two examples of Gram-positive bacteria against which the essential oil was evaluated for antibacterial activity. Gram-negative microorganisms such as Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC25922), and yeast Candida albicans were also evaluated for antimicrobial activity. The essential oil was assessed further against human liver (HEPG-2) and breast (MCF7) cell lines for anticancer properties. The findings suggest that, compared to the control, cardamom essential oil exhibits a significant zone of inhibition against all types of microbes except Pseudomonas aeruginosa. Additionally, for anti-cancer actions, the IC50 values were 42.3 µg/ml for MCF7 and 54 µg/ml for HEPG-2 cell lines, while IC90 results for MCF7 were 68.9 µg/ml and for HEPG-2 cell line were 80.7 µg/ml. The essential oil was developed in functional coating to preserve the postharvest mango fruit for 60 days at cold storage. The treated fruit showed reduced weight loss (10%), with a relative reduction of 78% compared to the control, chilling injury incidence (2.5%) at day 45, and rind pitting (3%) at day 30 compared to the control. This therapeutic plant may yield novel compounds for broad-spectrum antimicrobial and anticancer medicines and be transformed into economical and secure standardized herbal products.